Saigon's Edge : On the Margins of Ho Chi Minh City - Harms, Erik (Anthropologist) (Book collections on Project MUSE., 2010)
Much of the world's population inhabits the urban fringe, an area that is neither fully rural nor urban. Hoc Mon, a district that lies along a key transport corridor on the outskirts of Ho Chi Minh City, epitomizes one of those places. In "Saigon's Edge," Erik Harms explores life in Hoc Mon, putting forth a revealing perspective on how rapid urbanization impacts the people who live at the intersection of rural and urban worlds. Unlike the idealized Vietnamese model of urban space, Hoc Mon is between worlds, neither outside nor inside but always uncomfortably both. With particular att.